By Convolution Theorem :
"\\\\\nL^{-1}\\{F_{1}(s).F_{2}(s)\\}=\\int_0^tF_{1}(u).F_{2}(t-u) \\;du"
Here,we need to evaluate "L^{-1}\\{\\dfrac{1}{(s+1)(s+2)^2}\\}=L^{-1}\\{\\dfrac{1}{s+1}.\\dfrac{1}{(s+2)^2}\\}" :
Step-1 : Take "F_1(s)=\\dfrac{1}{(s+1)} \\;and\\; F_2(s)=\\dfrac{1}{(s+2)^2}"
Step-2 : "L^{-1}\\{F_1(s)\\}=L^{-1}\\{\\dfrac{1}{(s+1)}\\}"
Using the properties of inverse laplace transform : "L^{-1}\\{\\dfrac{1}{s-a}\\}=e^{at}\\;\\;and\\;\\;L^{-1}\\{\\dfrac{1}{s^n}\\}=\\dfrac{t^{n-1}}{(n-1)!}"
"\\therefore L^{-1}\\{F_1(s)\\}= L^{-1}\\{\\dfrac{1}{(s+1)}\\}=e^{-1.t}=e^{-t}=\\mathbf{f_1(t)}\\;and"
"L^{-1}\\{F_2(s)\\}=L^{-1}\\{\\dfrac{1}{(s+2)^2}\\}=e^{-2t}L^{-1}\\{\\dfrac{1}{s^2}\\}"
"\\implies L^{-1}\\{F_2(s)\\}=e^{-2t}.\\dfrac{t^{2-1}}{(2-1)!}=e^{-2t}.\\dfrac{t}{1!}=te^{-2t}=\\mathbf{f_2(t)}"
By using the convolution formula,we have -
"L^{-1}\\{\\dfrac{1}{(s+1)(s+2)^2}\\}=L^{-1}\\{\\dfrac{1}{s+1}.\\dfrac{1}{(s+2)^2}\\}"
"=\\int_0^t\\mathbf{f_1(u).f_2{(t-u)du}}"
"=\\int_0^te^{-u}.(t-u).e^{-2(t-u)}du"
"=\\int_0^t(t-u).e^{-u-2t+2u}du"
"=\\int_0^t(t-u).e^{u-2t}du=e^{-2t}\\int_0^t(t-u)e^udu"
"=e^{-2t}[t.\\int_0^te^udu-\\int_0^tue^udu]"
"=e^{-2t}\\bigg[t.\\bigg[e^u\\bigg]_0^t-\\bigg[u.\\int e^udu-\\int \\bigg(\\dfrac{d}{du}(u).\\int e^udu\\bigg)du\\bigg]_0^t\\bigg]"
"=e^{-2t}\\bigg[t.[e^t-e^0]-\\bigg[u.e^u-\\int\\bigg(1.e^u\\bigg)du\\bigg]_0^t\\bigg]"
"=e^{-2t}\\bigg[t.[e^t-1]-\\bigg[ue^u-e^u\\bigg]_0^t\\bigg]"
"=e^{-2t}\\bigg[te^t-t-\\bigg[(te^t-e^t)-(0-e^0)\\bigg]\\bigg]"
"=e^{-2t}\\bigg[te^t-t-\\bigg[(te^t-e^t)+1)\\bigg]\\bigg]"
"=e^{-2t}\\bigg[te^t-t-te^t+e^t-1\\bigg]=e^{-2t}(e^t-t-1)" .............Ans.
Comments
Leave a comment